A comparative study of morphometric parameters of knee using magnetic resonance imaging in different population groups - Ivan James Prithishkumar; Hephzibah Paul; Abdul Samad Punekar; Jeyaseelan Lakshmanan; Ali Albelooshi (Wolters Kluwer Medknow Publications, 2024)
Background: The design of majority of commercially available knee implants has their basis on data obtained from the European population. Anthropometric research has demonstrated a difference in the shape and size of proximal tibia and distal femur between the genders and ethnic groups. Underfit or overhang of prosthetic components can result in poor clinical and functional outcomes with need for revision. This study compares the dimensions of the knee in multiple racial groups to observe if significant racial and gender differences occur. Methodology: Morphometric parameters of the knee of adult patients (>18 years) in four population groups (Native Emirati, East Asian, Indian, and Caucasian) were measured using magnetic resonance imaging. Knee parameters were obtained from 368 patients (179 females and 189 males). Results: Males have larger femoral and tibial parameters compared to females (P < 0.01). For any specified anteroposterior length of knee, females demonstrate narrower mediolateral widths compared to males. Significant differences exist in knee parameters between the racial groups in both genders (P < 0.01). Conclusion: Adult knee parameters show significant variation between the genders and racial groups showing strong evidence for a race- and gender-specific knee arthroplasty system.